2017
DOI: 10.5194/acp-2017-174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of ambient ammonia in particulate ammonium formation at a rural site in the North China Plain

Abstract: <p><strong>Abstract.</strong> The real-time measurements of NH<sub>3</sub> and trace gases were conducted, in conjunction with semi-continuous measurements of water-soluble ions in PM<sub>2.5</sub> at a rural site in the North China Plain (NCP) from May to September 2013 in order to better understand of chemical characteristics for ammonia, and of the impact on formation of secondary ammonium aerosols in the NCP. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…According to the distribution of observed concentrations during haze in China, the threshold for the NH 3 coexistence condition is set as 15 ppb (Meng et al, 2018), and the threshold concentration for NO 2 coexistence is set as 30 ppb in this study. The times when NO 2 and NH 3 are below their thresholds are few (<5%) (See Fig.S3).…”
Section: Development Of a New Parameterization Methods Of So 2 Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…According to the distribution of observed concentrations during haze in China, the threshold for the NH 3 coexistence condition is set as 15 ppb (Meng et al, 2018), and the threshold concentration for NO 2 coexistence is set as 30 ppb in this study. The times when NO 2 and NH 3 are below their thresholds are few (<5%) (See Fig.S3).…”
Section: Development Of a New Parameterization Methods Of So 2 Uptakementioning
confidence: 99%
“…High emission of NH 3 and NO 2 in China and other developing countries (Wang et al, 2016) may result in significant synergistic effects in heterogeneous formation of sulfate and contribute to haze formation (Fu et al, 2017;He et al, 2014). Abundance of NH 3 (maximum concentration higher than 100 ppb) (Meng et al, 2018;Pan et al, 2012Pan et al, , 2018Wen et al, 2015) and strong correlations between the peak levels of fine particles and large increases in NH 3 concentrations (Liu et al, 2015a;Ye et al, 2011) were usually observed in the heavy haze condition. Therefore, investigating the heterogeneous reaction of SO 2 at different RHs and the coexistence of NH 3 is important to improve the simulation of SO 4 2− in air quality models.…”
Section: Introductionmentioning
confidence: 99%
“…1). Meng et al (2018) reported that there was a lag in the results of the LGR ammonia analyzer, and hourly average could reduce this influence. NH 3 measured by the LGR ammonia analyzer tracked well with the measurement at 102 m on the BMT from an open path quantum cascade-laser (QCL)-based NH 3 sensor (Aerodyne Research Inc., USA) using a 3 m fast-response counter-flow impactor inlet, with R 2 = 0.70, slope = 0.89 ( Fig.…”
Section: Ground Measurementsmentioning
confidence: 99%
“…This is attributed to the uniform generation of particulate matter in all the stream sections. There are a lot of agricultural activities (crop agriculture, livestock rearing, fish rearing) in the upstream and midstream sections of the river[15] [38] which deposit high amounts of suspended particles in the river while wastes generated from Mbarara municipality are the main contributors of suspended particles in the downstream of the river.…”
mentioning
confidence: 99%